Reingeniería de procesos para el restaurante El Cangrejo Criollo de la ciudad de Guayaquil, provincia del Guayas - Argudo Rivas, Liza Verónica (2017)
The development of this project has as objective to make a reenginering of the process for the “Cangrejo Criollo” restaurant located in the downtown of Guayaquil city, which has been in the ecuadorian market for 26 years; being pioneers in the creation of crabs plates. The establishment continues working due to the the good quality of its products as well as the curstomer service of the owner and his followers. It was reached to intervine the enterprise because of the used concepts of reenginering and processes; it was possible by using the research, deductive, analytical and descriptive methods. Also they needed to employ some techniques such as the observation, the interview with the owner of the Enterprise and surveys which were answered by 13 employees and the clients that visited the restaurant, having as an average 376 people. The following project was made meeting and investigating each one of the processes that “Cangrejo Criollo” restaurant has in the present. It could be observed that the time was used correctly for every action in order to be improved. As a sample it is taken the organizational structure,if it were very well organized, it would have better definied roles and specific functions for each worker, as well as the quality improvement of the products would increase through setting up a correct communication among the representatives of every area of the enterprise. In the restaurants’ business the basic processes are based on buying raw material, that must have its properly reception and its production until creating the product for selling. Then, the product is stored, invoiced, attached to a contable registration and available for the customers. The processes were studied step-by-step and some of them were redesigned, likewise two new processes were created: the post-selling and pro environment. This proposal will allow the enterprise to save 295 minutes, which can be used by the workers for other activities, it is also pretended to reduce the expenditures because of their high prices, due to it will benefit the restaurant. Another important point is the reestablishment of the employees’ roles that are detailed in the functions’ guide. At last, the conclusion was done focusing on the determined objectives and the necessary recommendations given to the Enterprise. The summary of the project was also generated as well as the bibliography and the annexes; which will be the supporting for the thesis understanding.